ANTESEDENT OF PARTNER PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING: Case Study of Gojek Drivers in Bali Province - Putu Dicky Fernaldi Setiawan; R Tri Priyono Budi Santoso; Yeyen Komalasari; Christimulia Purnama Trimurti (Universitas Bina Taruna Gorontalo, 2024)
This study aims to investigate the influence of work-life balance and flexible work arrangements on partner performance, with job satisfaction as an intervening variable. The research focuses on Gojek drivers in the province of Bali. The study employs a quantitative approach through a survey method to gather data from a sample of Gojek drivers. Data analysis will be conducted using Partial Least Squares (PLS), which constitutes a component of the Structural Equation Modeling (SEM) framework. The results showed that higher levels of job satisfaction contribute to improved performance, while lower levels of job satisfaction lead to decreased performance. Additionally, work-life balance positively and significantly affects performance through job satisfaction as an intervening variable among Gojek partner drivers in Bali Province. This indicates that achieving a good work-life balance can create job satisfaction, ultimately enhancing the performance of Gojek partner drivers in Bali Province. Similarly, effective implementation of flexible work arrangements positively and significantly influences performance through job satisfaction as an intervening variable among Gojek partner drivers in Bali Province. The findings of this study are expected to contribute to the understanding of how work-life balance and flexible work arrangements, particularly in the context of Gojek drivers in Bali